Oficios e cargos na documentación medieval do mosteiro de San Andrés de Vega de Espinareda (León) - Giménez Eguíbar, Patricia; Sánchez González de Herrero, Mª Nieves (Madrygal. Revista de Estudios Gallegos, 2019)
The goal of this paper is to analyze lexis from tradesmen, civil professions and clergy appointments contained in the medieval documents of the 13th-15th centuries from the monastery of San Andrés de Vega de Espinareda (El Bierzo, León). We distinguish between civil and ecclesiastical positions (merino, mayordomo, alcalde, pregonero, arcediano, canónigo, capellán, racionero and so on) and trades related to different areas, such as public notaries (notarios, escribanos), courts (juez árbitro, alguacil), and those of a more domestic scope, such as handicrafts and artisans dedicated to cattle and agricultural tasks (acemileros, vaqueros or molineros), to those related to food (cilleros, obedenciales y carniceros), clothing and footwear manufacturing (alfayates, tecedores, peleteros, zapateros), textile production (traperos, colcheros y tanegeros, ‘tanners’), smithery (correeros, tayadores y ferreros o ferradores), construction (pedreros, carpinteros), or commerce (tenderos y mercadores). Due to frequency and dialectical implications, we pay special attention to the trades formed with the suffix -eiro / -ero. The analysis of the phonetic and lexical levels confirms the lack of clear linguistic boundaries in the written record of the geographical area studied.
Keywords: Historical Lexicography; Dialect Contact; Galician; Leonese